Archaeozoology in Mainland Southeast Asia: Changing Methodology and Pleistocene to Holocene Forager Subsistence Patterns in Thailand and Peninsular Malaysia. (10th July 2015) - Conrad, Cyler
Meta-analysis of archaeozoological data from 28 prehistoric sites in Thailand and Peninsular Malaysia indicate that turtle (hard-shell, soft-shell and tortoise) and mollusc exploitation dominate the late Pleistocene and Holocene hunter-gatherer record. A total of 163 taxonomic classifications provide 29, 842 identified specimens in this dataset. Using nestedness and squared chord distance metrics, results indicate that narrowing diet breadth and similar faunal composition is broadly characteristic of this region through time. A historical review of recording techniques indicates that while minimum number of individual (MNI) faunal quantification remained abundant during the twentieth century, number of identified specimen (NISP) quantification is more prevalent today. Synthesis of taxonomic composition suggests that Peninsular Malaysian sites have a higher abundance of wild boar (Suidae) in relation to Thailand sites that have a higher abundance of deer (Cervidae). Turtles and molluscs appear at almost every site in relative high occurrence and abundance. Future archaeozoological research should focus on standardizing quantification techniques, and providing fine-grained identification of turtle specimens to more accurately investigate shifting subsistence strategies, paleoenvironmental change, and seasonal occupation of sites throughout mainland Southeast Asia during the Pleistocene and Holocene. Social Media: Archaeofaunal overview of Thai-Malay sites refocuses our understanding of prehistoric subsistence; turtles and molluscs dominate.